Teamwork skills assessment for STEM Project-Based Learnig - Noly Shofiyah; Fitria Eka Wulandari; Metatia Intan Mauliana; Puspitasari Putri Pambayun (Jurnal Penelitian Pendidikan IPA, 2022)
This study developed an instrument for assessing undergraduate students’ teamwork skills in designing and creating team product in the context of science, technology, engineering, and mathematics (STEM) learning. The development stage follows the stages of the R & D method developed by Barg and Gall. Teamwork skills instrument that has been declared valid qualitatively and quantitively as well as are implemented in STEM project-based learning using one shot-case study design in three different courses. The teamwork skills are measured based on self-assessments, peer-assessment, and facilitator evaluations. The scores obtained from three sources of assessment are analyzed, using descriptive statistics and ANOVA. The results show that the teamwork skill instrument is valid and reliable to measure the students’ collaborative skills in the STEM Project. In addition, the results of the three assessments showed that The STEM project-based learning is effectively able to train students' teamwork skills